“Assessment of Sperm Parameters in Albino Wistar Rats Treated with Benincasa hispida Seed Extract and Coenzyme Q10” - Sharma, Savita; Azeem, Mohd Umar; Singh, Sonalika; Goswami, Anjali (Journal of Neonatal Surgery, 2025)
Infertility, a rising global health concern, affects nearly 15–20% of couples, with male factors contributing to about half of all cases. Central to male fertility are sperm parameters, including count, motility, morphology, and viability, which collectively determine reproductive potential. Oxidative stress, lifestyle factors, and testicular dysfunction significantly impair these indices, underscoring the need for novel, safe, and effective therapeutic interventions. Natural products rich in antioxidants have emerged as promising alternatives to conventional therapies. The present study evaluated the effects of Benincasa hispida seed extract in combination with Coenzyme Q10 (CoQ10) on semen quality in adult male albino Wistar rats. A total of 24 rats were randomly divided into four groups: control (vehicle only), low dose (100 mg/kg B. hispida + 10 mg/kg CoQ10), medium dose (150 mg/kg B. hispida + 10 mg/kg CoQ10), and high dose (200 mg/kg B. hispida + 10 mg/kg CoQ10). Treatments were administered orally for 60 days, corresponding to at least one complete spermatogenic cycle. Semen analysis revealed a clear dose-dependent improvement in all measured parameters. Compared to the control group, treated groups demonstrated significant increases in sperm count (from 52.0 to 95.0 million/mL), total motility (70% to 93%), progressive motility (60% to 78%), viability (72% to 95%), and normal morphology (80% to 98%). Additionally, semen volume improved (0.6 to 0.88 mL), and pH shifted favorably (7.2 to 7.7). The most pronounced benefits were observed at the 200 mg/kg dose, although the 150 mg/kg dose also exhibited near-optimal effects. These findings suggest that B. hispida seed extract and CoQ10 synergistically enhance sperm quality by reducing oxidative stress, supporting mitochondrial function, and promoting spermatogenesis. The study highlights the potential of combining phytotherapeutics and nutraceuticals as safe, effective strategies for managing male infertility.